Doping Induced Tailoring in the Morphology, Band-Gap and Ferromagnetic Properties of Biocompatible ZnO Nanowires, Nanorods and Nanoparticles - Iqbal, Javed; Jan, Tariq; Ronghai, Yu; Naqvi, Sajjad Haider; Ahmad, Ishaq (Nano-Micro Letters, 2014)
The modification of nanostructured materials is of great interest due to controllable and unusual inherent properties in such materials. Single phase Fe doped ZnO nanostructures have been fabricated through simple, versatile and quick low temperature solution route with reproducible results. The amount of Fe dopant is found to play a significant role for the growth of crystal dimension. The effect of changes in the morphology can be obviously observed in the structural and micro-structural investigations, which may be due to a driving force induced by dipole-dipole interaction. The band gap of ZnO nanostructures is highly shifted towards the visible range with increase of Fe contents, while ferromagnetic properties have been significantly improved. The prepared nanostructures have been found to be nontoxic to SH-SY5Y Cells. The present study clearly indicates that the Fe doping provides an effective way of tailoring the crystal dimension, optical band-gap and ferromagnetic properties of ZnO nanostructure-materials with nontoxic nature, which make them potential for visible light activated photocatalyst to overcome environmental pollution, fabricate spintronics devices and biosafe drug delivery agent.